Development of Video Tutorial Media on Virgin Hair Coloring Single Application Technique in Beauty Student of AKP Galang Vocational School - Dian Maya Sari; Rossy Luckita Sasmita; Tri Dia Suci (Universitas Muhammadiyah Enrekang, 2024)
This research aims to determine the feasibility of video tutorial learning media in single application technique virgin hair coloring for beauty students at AKP Galang Vocational School. This research uses research and development methods), and aims to develop and test a product produced for learning media. The research stages are conducting needs analysis, product design, product validation, product testing and final production. The validation stage is divided into two, namely material validation and media validation, material validation is carried out by three material experts, and media validation is carried out by three media experts. The research results show: (1) Students stated that 87% needed video tutorial media, (2) Teachers stated that 98% needed video tutorial media, (3) Expert test material for single application virgin hair coloring technique was in exellent criteria (96%), (4) Media expert testing of video tutorial products is in excellent criteria (95%), (5) Trials in small groups are in excellent criteria (90%), (6) Trials in medium groups are in excellent criteria (92%), (7) Trials in large groups were in excellent criteria (95%). The results concluded that the video tutorial on virgin hair coloring with the single application technique was declared feasible and could be considered for use in learning activities by teachers and students.